Natural durability of Cedrus atlantica wood related to the bioactivity of its essential oil against wood decaying fungi - Fidah, Abdelwahed; Salhi, Noura; Rahouti, Mohamed; Kabouchi, Bousselham; Ziani, Mohsine; Aberchane, Mohamed; Famiri, Abderrahim (Maderas. Ciencia y Tecnología, 2016)
The Atlas cedar, Cedrus atlantica is a resinous species of Pinaceae originated from North Africa and well known for its noble timber. This work was conducted to assess the natural durability of its wood, to study the chemical composition of essential oil extracted from its sawdust wood and to test the bioactivity of this essential oil against four wood decaying fungi: Gloeophyllum trabeum, Oligoporus placenta, Coniophora puteana and Trametes versicolor. The assessment of natural durability of wood was conducted according to the methods described in the European standards, CEN/TS 15083-1 and NF EN 350-1. Mass losses of wood specimens, after 16 weeks of exposure to fungi attack, in laboratory test, showed that Cedrus atlantica wood is very durable to durable against wood decay fungi attack. The extraction of essential oil from sawdust by hydro-distillation yielded about 3,35% and the chemical analysis of this essential oil by GC-MS showed that E-γ-Atlantone (19,73%); E-α- Atlantone (16,86%), 5-Isocedranol (11,68%); 9-iso-Thujopsanone (4,45%); Cedranone (4,13%) and Z α- Atlantone (4,02%) were the main major identified components. The antifungal activity tested by the direct contact technique on agar medium showed a strong inhibition of wood decaying fungi, especially Gloeophyllum trabeum inhibited at 1/1000 v/v concentration.